Sealing agent reduces formation of single and dual-species biofilms of Candida albicans and Enterococcus faecalis on screw joints at the abutment/implant interface - de Sousa, Cecília Alves [UNESP]; Conforte, Jadison Junio [UNESP]; Caiaffa, Karina Sampaio [UNESP]; Duque, Cristiane [UNESP]; Assunção, Wirley Gonçalves [UNESP] (Public Library of Science (PLoS), 2019)
The aim of this research was to evaluate the efficacy of a commercial sealing agent at the abutment/implant interface against microleakage of single and dual-species biofilms of Candida albicans and Enterococcus faecalis into external hexagon (EH) and Morse taper (MT) prosthetic connections. A total of 216 samples of implants and their abutments were tested. Six groups (n = 36) were evaluated based on biofilm and period of incubation (7 and 14 days). The implant connections EH and MT (n = 18) were divided according to the use of the material (n = 9) (EH-T and MT-T: with the sealing agent; EH-C and MT-C: control). The biofilms were analyzed by microbial counting (CFU/mL) and SEM analysis and photographs of the material in the screw joints were also taken. Data were analyzed by Student t test, two-way ANOVA and Bonferroni test. For the single-species biofilms, there was a significant reduction in the growth of E. faecalis when compared MT-C and MT-T or EH-C and EH-T at 7 and 14 days. The same was observed for C. albicans biofilms. For dual-species biofilms of E. faecalis and C. albicans, the sealing agent was more effective in preventing microbial infiltration into the MT connection at 14 days, while microbial infiltration did not occur into EH connections even in absence of the sealing agent for both periods of evaluation. Overall, these data suggest that the presence of the sealing agent reduces or eliminates the microleakage of E. faecalis and C. albicans biofilms into the implants regardless of the period of incubation.